GPS satellites parallel C/A code generation - R. K. Apikyan (ՀՀ ԳԱԱ հրատ.)
In the GPS system, a signal, is modulated with C/A code. The C/A codes belong to PRN (pseudo random numbers) code family and is repeated in every millisecond of the GPS signal. Each millisecond of the signal contains 1024 chips (or bits) of a C/A code. GPS համակարգում ազդանշանը մոդուլվում է C/A կոդով։ C/A կոդերը պատկանում են PRN (քվազի պատահական կոդեր) կոդերի ընտանիքին և կրկնվում են GPS ազդանշանի յուրաքանչյուր 1 մվ-ում։ В системе GPS сигнал модулируется с помощью кода C/A. Коды C/A принадлежат к семейству кодов PRN (псевдослучайных чисел) и повторяются каждую миллисекунду в сигнале GPS.
Keywords: Electrical engineering; Electronics; Nuclear engineering; Technology